LEGAL REGULATION OF REMOTE WORK IN UKRAINE: CONFLICTS IN LEGISLATION AND WAYS TO OVERCOME THEM - Vyshnovetska, Svitlana; Snisarenko, Ilona (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this article is to provide a comprehensive analysis of regulatory conflicts arising in the legal regulation of remote work in Ukraine, to clarify their impact on the implementation of the employees’ labour rights, and to identify ways to eliminate them through legislation, taking into account the current conditions of digitalisation, martial law and European standards. Research methods: analysis and synthesis of scientific sources and regulatory and legal acts, formal legal method for interpreting the legal norms, comparative legal method for Ukrainian and European legal regulation of remote work, systemic-structural method for identifying the conflicts between legislative norms, as well as legal modelling method for formulating the proposals to improve legislation. Results: the main conflicts in the legal regulation of remote work in Ukraine were identified, in particular, regarding the conclusion of the employment contracts, occupational safety, the employer control, working hours and compensation of expenses. Inconsistencies between the norms of the Constitution of Ukraine, the Labour Code of Ukraine and special laws, as well as the absence of clear rules for digital monitoring were defined. The European practices have been analysed and proposals have been formulated to eliminate these conflicts by introducing the electronic signatures, the declarative principle of joint liability, defining the limits of control and regulating compensation. Discussion: the impact of digitalisation on labour relations and the need to harmonise regulations on control, occupational safety and compensation with European standards in order to overcome existing conflicts. The study showed that the legal regulation of remote work in Ukraine is in its infancy and needs significant improvement. It was concluded that it is advisable to introduce the declarative principle of joint responsibility for safe working conditions, define clear limits of the employer control based on the principles of proportionality and respect for privacy, respect the employee’s right to “switch off” outside working hours, and developing the unified rules for calculating the compensation payments and exempting them from taxation within the established limit. The implementation of these proposals will harmonise the Ukrainian labour legislation with European standards, ensure a balance between the interests of the employees and the employers, and create an effective legal model for remote work that meets the challenges of the digital economy and wartime conditions.